Implementasi Mnemonic Learning dalam Menghafal Al-Qur’an dengan Metode Hanifida - Lalu M Baihaqi Thahir (AFKARINA: Jurnal Pendidikan Agama Islam, 2021)
This paper discusses mnemonic learning strategies for memorizing the Qur'an. Al-Qur'an is the spirit for Muslims, if the spirit is lost then it is the same as Muslims have died. Therefore, the Qur'an is very important for Muslims to memorize, learn, and practice it. Memorization is the realm of the brain, related to remembering and forgetting. To achieve memorization with maximum results, a method is needed to achieve this goal, because if the method is wrong then of course the goal will be difficult to achieve. Mnemonic Learning as a method of memorizing has many strategies to improve memorization, including five Mnemonic strategies implemented at the Supercamp Hanifida Islamic Boarding School, namely the Number and Shape Method, Visual Imagery Method, Narrative Technique, Linking Word Method (Word link), and Loci method.